Electronic Digital Indentification (E-KTP) as an Element of E-Democracy in Indonesia - Daud, Irna Irmalina; Sumaryana, Asep; Nurasa, Heru; Susanti, Elisa (KnE Social Sciences, 2022)
Indonesia has started implementing e-democracy in the general election process by determining e-KTP as a voter requirement. This paper explored Indonesia’s efforts to develop e-democracy. Qualitative methods were used by applying desk research and triangulation methods. The results demonstrated that Indonesia is on the right track to develop e-democracy. Furthermore, various electoral processes have used different kinds of electronic media. In the future, it could be possible to implement e-voting and e-petition. Some challenges remain, including the digital divide, protecting private data, and resiliance of the system against hackers. Keywords: e-democracy, e-KTP, e-government, society 5.0